Synthetic Biology: The New Era - Samudra Guha; Joyeeta Talukdar; Abhibrato Karmakar; Sandeep Goswami; Arun Kumar; Ruby Dhar; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2022)
Synthetic biology is an emerging discipline of science, at the intersection of biology, engineering, and chemistry that involves redesigning organisms to have new phenotypes and customized abilities. While synthetic biology seems to have originated from genetic engineering, over the years, it has matured as well as diverged from it. It involves not just the transfer of genes from one or cell to another creating some variants, it also involves the assembly of an altogether novel organism or cell created part by part by the assembly of individual components of the desired function in a logical fashion. In this minireview, we will explore this new discipline and its possible applications and future promises to serve the humanity